Comparison and Cost Analysis of Soft Soil Foundation Treatment Schemes in Port Construction - Qiang Ren (Advances in Civil Engineering)
Due to the characteristics of soft soil foundations in port engineering construction, there is a problem of insufficient bearing capacity, which needs to be treated. This paper analyzes the construction process and key points of the dynamic compaction method, vacuum preloading method, and vibroflotation method, and expounds on the advantages and disadvantages. The cost of different methods is compared. It can be seen that compared with other methods, the vibration impact method has a simple construction process and low cost.